Homogenization of hyperbolic damped stochastic wave equations - Fouetio, Aurelien; Woukeng, Jean Louis (Acta mathematicae applicatae sinica. English series, 2018)
For a family of linear hyperbolic damped stochastic wave equations with rapidly oscillating coefficients, we establish the homogenization result by using the sigma-convergence method. This is achieved under an abstract assumption covering special cases like the periodicity, the almost periodicity and some others.